Open source software in Information Technology education - Mohamed, Norshidah; , Muhammad Sadry; Hussein, Ramlah (Institute of Electrical and Electronics Engineers (IEEE), 2009)
As Malaysia strengthens its position as an outsourcing hub, there continues to be many job opportunities in information technology in Malaysia. This paper looks at the ranking of open source software skills in demand. Further, it provides insights into graduates' perception of usefulness for courses using open source software versus proprietary software at a local institution of higher learning.